Anxiety and Information Seeking: Evidence From Large-Scale Mouse Tracking - Youngmann, Brit; Yom-Tov, Elad (WWW, 2018)
People seeking information through search engines are assumed to behave similarly, regardless of the topic which they are searching. Here we use mouse tracking, which is correlated with gaze, to show that the information seeking patterns of people differ dramatically depending on their level of anxiety at the time of the search. We investigate the behavior of people during searches for medical symptoms, ranging from benign indications, where users are not usually anxious, to ones which could harbinger life-threatening conditions, where extreme anxiety is expected. We show that for the latter, 90% of people never saw more than the top 67% of the screen, compared to over 95% scanned by people seeking information on benign symptoms, even though relevant documents are similarly distributed in the results pages to these queries. Based on this observation, we develop a model which can predict the level of anxiety experienced by a user, using attributes derived from mouse tracking data and other user interactions. The model achieves Kendall's Tau of 0.48 with the medical severity of the symptoms searched. We show the importance of using information about the users? level of anxiety as predicted by the model, when measuring search engine performance. Our results prove that ignoring this information can lead to significant over-estimation of performance. Additionally, we show the utility of the model in three special instances: where multiple symptoms are searched concurrently; where the searcher has an underlying medical condition; and when users seek information on ways to commit suicide. In the latter, our results demonstrate the importance of help-line notices, and emphasize the need to measure the effective number of results seen by the user. Our results indicate that measures of relevance which use anxiety information can lead to more accurate understanding of the quality of search results, especially when delivering potentially life-saving information to users.